2019
DOI: 10.5194/isprs-archives-xlii-3-w6-169-2019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal Feature Extraction for Precise Maize Area Mapping Using Time-Series Sentinel 1a Sar Data

Abstract: <p><strong>Abstract.</strong> A research study was conducted to map maize area in Ariyalur and Perambalur districts of Tamil Nadu, India using multi-temporal features extracted from time-series Sentinel 1A SAR data. Multi-temporal Sentinel 1A GRD data at VV and VH polarizations and SLC products were acquired for the study area at 12 days interval and processed using MAPscape-RICE software. Multi-temporal Sentinel 1A data was used to identify the backscattering dB curve of maize crop. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The overall accuracy (>80%) and kappa score (>0.50) indicated that the assessment was of high quality. The results were in accordance with [28][29][30][31], who delineated the crop area estimation with high classification accuracy using multi-temporal Sentinel-1A data; this indicated the suitability of remote-sensing-based images for crop area estimation and monitoring for policy decisions, including crop insurance.…”
Section: Peanut Area and Accuracy Assessmentsupporting
confidence: 87%
“…The overall accuracy (>80%) and kappa score (>0.50) indicated that the assessment was of high quality. The results were in accordance with [28][29][30][31], who delineated the crop area estimation with high classification accuracy using multi-temporal Sentinel-1A data; this indicated the suitability of remote-sensing-based images for crop area estimation and monitoring for policy decisions, including crop insurance.…”
Section: Peanut Area and Accuracy Assessmentsupporting
confidence: 87%
“…It has been widely used to estimate the area of major crops like paddy, maize, cotton, mango and banana. (Pazhanivelan et al, 2015;Setiyono et al, 2019;Sudarmanian et al, 2019;Kannan et al, 2021;Ramalingam et al, 2019;Venkatesan et al, 2019;Kaliaperumal et al, 2019;Karthikkumar et al, 2019). This study is to estimate the area and distribution of paddy in the Cauvery Delta region of Tamil Nadu during Samba season 2020-2021.…”
Section: S518mentioning
confidence: 99%